(untitled) (Studia theodisca, 2014)
This paper focuses on Hölderlin’s Italian imagery, which has scarcely been investigated in previous research. Both as a geographical and metaphorical locus and as a literary and linguistic reference, Italy emerges as being more intensely present in Hölderlin’s life and work than has hitherto been assumed.